Takhrij and Syarah Hadith on Chemistry: Islamic Perspective on Chemical-Based Medicines - Adzkya Al Qudsiyyah Burhan; Wahyudin Darmalaksana; Eko Prabowo Hadisantoso; Iu Rusliana (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet. about chemical-based drugs. This research method is qualitative through the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this research is about the controversy in the community regarding chemical-based drugs as well as the halal law and the prohibition of chemical-based drugs according to Islamic views. The conclusion of this research is takhrij and syarah hadith of the Prophet. about chemical-based drugs with chemical analysis that chemical drugs are effective in curing diseases, however, not all chemical-based drugs are good to use, some chemical-based drugs are dangerous to health.